Dissecting the association between gut microbiota and liver cancer in European and East Asian populations using Mendelian randomization analysis - Jiang, Hua; Song, Tianjun; Li, Zhongyi; An, Lingxuan; He, Chiyi; Zheng, Kai (Frontiers in Microbiology, 2023)
Ample evidence suggests an important role of the gut microbiome in liver cancer, but the causal relationship between gut microbiome and liver cancer is unclear. This study employed Mendelian randomization (MR) analysis to examine the causal relationship between the gut microbiome and liver cancer in European and East Asian populations.We sourced genetic variants linked to gut microbiota from the MiBioGen consortium meta-analysis, and procured liver cancer genome-wide association study (GWAS) summary data from the FinnGen consortium and Biobank Japan.We employed the inverse variance weighted method for primary statistical analysis, fortified by several sensitivity analyses such as MR-PRESSO, MR-Egger regression, weighted median, weighted mode, and maximum likelihood methods for rigorous results. We also evaluated heterogeneity and horizontal pleiotropy.The study examined an extensive set of gut microbiota, including 131 genera, 35 families, 20 orders, 16 classes, and 9 phyla. In Europeans, ten gut microbiota types displayed a suggestive association with liver cancer (P < 0.05).Notably, Oscillospira and Mollicutes RF9 exhibited a statistically significant Gut microbiota and liver cancer 3 / 29 positive association with liver cancer risk, with odds ratios (OR) of 2.59 (95% CI 1.36-4.95) and 2.03 (95% CI 1.21-3.40), respectively, after adjusting for multiple testing. In East Asians, while six microbial types demonstrated suggestive associations with liver cancer, only Oscillibacter displayed a statistically significant positive association (OR = 1.56, 95% CI 1.11-2.19) with an FDR < 0.05. Sensitivity analyses reinforced these findings despite variations in P-values.This study provides evidence for a causal relationship between specific gut microbiota and liver cancer, enhancing the understanding of the role of the gut microbiome in liver cancer and may offer new avenues for preventive and therapeutic strategies.